Diogenio Bigaglia and His Dixit Dominus. (September 2022) - Talbot, Michael
Abstract: In his own time Diogenio Bigaglia (1678–1745) was viewed as the equal of Venice's three great amateur musicians active during the first half of the eighteenth century (Tomaso Albinoni, Alessandro Marcello and Benedetto Marcello), but he is largely forgotten today. Part of the reason is the secluded, uneventful life he led as a Benedictine monk at the abbey of San Giorgio Maggiore. This article analyses an impressive early work: a twelve-movement Dixit Dominus probably composed between 1700 and 1710. This work occupies the borderland between late seventeenth-century musical practice and the more progressive musical forms, styles and techniques introduced in the early eighteenth century. It survives in a late eighteenth-century copy by the Venetian copisteria of Giuseppe Baldan that probably passed via Domenico Dragonetti to Vincent Novello, who donated it to the British Museum in 1843. The music contains many attractive features, including an imaginative use of the instruments and dextrous counterpoint, pointing the way forward to the choral masterpieces of Bigaglia's maturity.